Clinical application of intubation-free anesthesia in radical resection of lung cancer - Liu, Zhenhai; Ren, Shengjie; Liu, Ning; Luo, Yanhua (Frontiers in Medicine, 2023)
Background: In recent years, video-assisted transthoracic surgery (VATS) has become increasingly widespread. However, the implementation of VATS requires the assistance with lung isolation techniques. Spontaneous breathing with laryngeal masks is also increasingly used in VATS. However, evidence on the characteristics of intubated anesthesia is insufficient. Objective: This study aimed to explore whether intubation-free anesthesia has more advantages than other intubation methods in the clinical setting. Methods: Patients with lung tumors who underwent VATS in our hospital between June 2022 and October 2022 were included in the study. Perioperative data of patients, including basic information, intraoperative hemodynamic changes, postoperative inflammatory indicators, and adverse reactions were obtained through the electronic medical record system. According to the protocol of airway management during anesthesia, participants were divided into the following groups: laryngeal mask with spontaneous breathing group (LMSB group), laryngeal mask combined with bronchial blocker group (LM+BB group), double-lumen tube group (DLT group), and tracheal tube combined with bronchial blocker group (TT+BB group). All data were analyzed using SPSS 25.0 software. Results: At baseline, patients in the LMSB and LM+BB groups had a lower body weight (P=0.024). Systolic blood pressure (SBP), diastolic BP (DBP), and heart rate (HR) were significantly higher in the DLT group than in the nonintubated group during surgery (SBP: T4 P=0.021, T5 P <0.001, T6 P<0.001, T7 P=0.004; DBP: T5 P <0.001, T6 P<0.001, T7 P=0.001; HR: T5 P <0.001, T6 P=0.007, T7 P<0.001). The input fluid (P=0.009), urine output (P=0.010), surgery duration (P=0.035), and procalcitonin levels (P=0.024) of the DLT group were also significantly higher than those of the other groups. The recovery duration of the LMSB group was significantly longer (P=0.003) and the incidence of postoperative adverse reactions, mainly atelectasis, was higher (P=0.012) than those of the other groups. Conclusions: Although the intubation-free anesthesia has less stimulation during operation and less postoperative inflammatory response, it has obvious adverse reactions after operation, which may be not the best anesthesia scheme for radical resection of lung cancer in VATS.